(7x-3)(-2)+x=0

Simple and best practice solution for (7x-3)(-2)+x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-3)(-2)+x=0 equation:


Simplifying
(7x + -3)(-2) + x = 0

Reorder the terms:
(-3 + 7x)(-2) + x = 0

Reorder the terms for easier multiplication:
-2(-3 + 7x) + x = 0
(-3 * -2 + 7x * -2) + x = 0
(6 + -14x) + x = 0

Combine like terms: -14x + x = -13x
6 + -13x = 0

Solving
6 + -13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -13x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -13x = 0 + -6
-13x = 0 + -6

Combine like terms: 0 + -6 = -6
-13x = -6

Divide each side by '-13'.
x = 0.4615384615

Simplifying
x = 0.4615384615

See similar equations:

| 3-12+7=10+x-3 | | 3x(2x-4)-1=-1 | | x+y=325 | | -9.6+x=-13.5 | | 22-7m= | | 5(x-2)=5-2x | | x-5.5=8.6 | | 21a^5+211a^3b^2+10ab^4=0 | | 5(4x+2)=3(6x+3) | | 17*n=51 | | 4(2x-3)=2(5x+2) | | 36-n=15 | | 5x-2x-7x-3x=18+6-24-6 | | 4(4x+5)=6(6x-3) | | 12=g/4-3 | | y(70-20y+10)=0 | | y(70-2y+10)=0 | | (2+y)(3y-8)=0 | | y(70-2+y+10)=0 | | a*6+7=11 | | 39xn=3 | | x(70-10)=0 | | 3(5-3x)=25 | | 39/:n=3 | | 70-20+y+10=0 | | 18+-1n=10 | | -3(-3)+2(-3)-3=0 | | 34xn=34 | | 3[d+12]=8-4d | | 9(-9)-10(-9)+9=0 | | (9)9-10(9)+9=0 | | -5x+3=6x-2 |

Equations solver categories